Plasma-corticosterone radioimmunoassay and levels in the neonate chick - Abdullah, Ramli; Gildersleeve, R.P.; Satterlee, D.G. (1980)
The objective was to develop and validate a rapid, precise plasma corticosterone radioimmunoassay using a commercially available antiserum, for use in Gallus domesticus. Sample preparation consisted of sequential 2,2,4-trimethylpentane and dichloromethane extraction to partition progestins and glucocorticoids, respectively. Progesterone, 11 beta-Hydroxyprogesterone, and deoxycorticosterone significantly cross reacted with the antiserum used. However, progesterone was effectively removed prior to assay by the 2,2,4-trimethylpentane plasma washings while 11 beta-Hydroxyprogesterone and deoxycorticosterone interference is doubtful for reasons discussed. Standard curve data showed a linear range from 0 to 150 pg by log-logit transformation with a 5 pg assay sensitivity. Mean percent unlabeled corticosterone recovery was 96% with intraassay and interassay coefficients of variation being 3.75 and 5.62%, respectively. The assay was utilized to characterize corticosterone fluctuations during day one post hatch in broiler chicks. Method of blood collection, rapid decapitation vs. heart stab, resulted in no difference in mean plasma corticosterone levels. Corticosterone levels differed over a 24 hr sampling period, such that highest levels were found upon receipt of the chicks at the hatchery (approximately 20 ng/ml) and 20 hr later (approximately 11 ng/ml). Lowest plasma corticosterone concentrations occurred from 10 to 14 hr (approximately 6 ng/ml) after receipt of the chicks.